Qualified volleyball players technical readiness development - Tinykov, A. B. (The Russian Journal of Physical Education and Sport, 2016)
A natural process of volleyball development, the rules of competitions change, sportsmanship improvement of the leading players condition the search for new directions of sports training system development. Special literature offers different approaches to the level of technical readiness increase among volleyball players of different qualifications, however, as a rule, only separate questions are considered, which doesn`t help to solve the problem in general. The article offers different directions of technical readiness indices increase among qualified volleyball players, the realization of which gives an opportunity to gain a new level of the training process organization. Research methods: scientific-methodical literature analysis and systematization, pedagogical experiment, survey, testing, statistical data manipulation. Materials. Theoretical importance substantiation of technical readiness level increase among qualified female volleyball players. Results. The author formulates the main conceptual theses, which help to realize the main principles of the training lessons organization, the essence of which is to deprive a player of the opportunity to fulfill a motor act with the deflection from a rational technique at every raining. It is important for a trainer and a volleyball player to realize, that the technique of the playing actions is created for each sportsman individually, taking into consideration his height-weight indices, the level of physical and functional readiness, the leading motional-coordinating qualities development. As the research results showed, most respondents (volleyball trainers) think that a modern methodology of sports training among qualified volleyball players doesn`t correspond to world standards of sportsmanship and demands improvement. The methodology is created of technical readiness level increase, which provides a creative atmosphere at the lessons and creates a positive psycho-emotional atmosphere, as the condition for original ideas appearance concerning the training process or the technique of a definite playing method development. The characteristics determination of each motor act was fulfilled taking into consideration individual indices of the training level, morphofunctional peculiarities, the level of motional-coordinating qualities development. Conclusion. The results of the pedagogical experiment showed the expediency of this methodology use, which is proved by a considerable improvement of technical and physical readiness indices among female volleyball players form the experimental group. A rational training lesson can`t provide wrong motor skill formation; a trainer should control the technique of each motor act in different situations of the training and competitive activity. At the same time, it is important that self-control can`t replace pedagogical control over spatio-temporal and spatio-power parameters of a motor act.